Childhood attachment and adult personality: A life history perspective. Issue 1 (2nd January 2019) - Young, Ethan S.; Simpson, Jeffry A.; Griskevicius, Vladas; Huelsnitz, Chloe O.; Fleck, Cory
Abstract: According to attachment theory, being securely attached to one's primary caregiver early in life should be related to personality adulthood. However, no studies to date have investigated this key premise using prospective data. To address this gap, we discuss evolutionary-based models of attachment and use them to examine how secure versus insecure children might score differently on Big 5 traits that underlie the meta-trait stability. We modeled data from Minnesota Longitudinal Study of Risk and Adaptation (N = 170), which has followed participants across 30 years. Participant's early attachment status was assessed in Ainsworth's Strange at 12 and 18 months and personality was assessed on Big 5 measures at age 32. Being securely attached early in childhood predicted three of the Big 5 traits known to tap the meta-trait stability. Specifically, participants rated as secure early in life scored higher on agreeableness and conscientiousness and lower on neuroticism in adulthood, whereas those rated as insecure scored lower on agreeableness and conscientiousness and higher on neuroticism. Exploratory mediation analyses revealed that neither adult attachment representations nor internalizing/externalizing symptoms mediated the association between early security and stability. The implications of these findings for understanding the origins of personality variation are discussed.